DIVERSIFIKASI RESIDU PRODUK OLAHAN HOME INDUSTRY SIRUP JERUK KALAMANSI DI KABUPATEN BENGKULU TENGAH - Evi Maryanti; Dyah Fitriani; Fathnur Sani (Universitas Bengkulu, 2018)
Community Service Activities for Residual Diversification of Processed Products Home Industry Syrup Kalamansi in Bengkulu Tengah has been completed. This activity aims to reduce the residual volume of unused Kalamansi syrup yields, the production of high value essential oils and various essential and economically valuable essential oil-based citrus oil products. In this activity we have conducted training on the way of extraction of essential oil from citrus peel residue and crude fiber (dregs) leftover of Kalamansi syrup using direct steam distillation method, followed by training of various essential oil based health products in form of aromatherapy roll oil, and Antiseptic liquid soap. From the results of the activities that have been done, the essential oil from the residue of Kalamansi syrup made of clear liquid smelling orange Kalamansi. It has also been produced several products made from active essential oil of orange Kalamansi such as wind oil roll on, liquid bath soap, lotion and liquid washing soap. The four products have a typical citrus scent Kalamansi, but need to be refined formula to produce a quality product and selling value. Keywords: Citrus Kalamansi, Steam Distillation, essential oils, wind aromatheraphy oil.